GRAPHICAL SOLUTION OF SYSTEMS OF EQUATIONS IN TWO-AND THREE-DIMENSIONAL SPACES USING MS EXCEL - Uzokov, Farxod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this article, methods for solving systems of equations using the graphical approach in MS Excel are presented. The theoretical foundations of the graphical solution method are explained, and the steps for using Excel functions are demonstrated step by step. As a practical example, systems of linear equations with two and three variables are analyzed, their graphs are constructed, and the point of intersection is determined.